Assessment of Clinical Characteristics and Outcomes of Liver Diseases Unique to Pregnancy at a Tertiary Hospital in Ethiopia: A Retrospective Cohort Study - Sintayehu Mekonnen; Henok Fisseha; Tewodros Getinet (International Journal of Hepatology)
Background. Liver disease is a rare complication of pregnancy that can lead to several consequences and require specific intervention with implications for both the mother and fetus. This study is aimed at assessing the clinical profile and associated complications of liver diseases unique to pregnancy at St. Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia. Methodology. This study is a retrospective cohort study of all identified cases admitted to the obstetrics ward and intensive care unit (ICU) from January 2018 to December 2020 at St. Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia. Medical records were reviewed for clinical features, biochemical profiles, and fetomaternal complications. Data were analyzed using SPSS version 26. A chi-square test was done to look for an association with a p value less than 0.05 considered statistically significant, and an odds ratio was determined to assess the effect size. Results. From 95 cases identified, preeclampsia/eclampsia with liver dysfunction accounted for 43 (45%), followed by hemolysis elevated liver enzyme and low platelet (HELLP syndrome) 35 (36.8%), hyperemesis gravidarum with liver dysfunction 9 (9.5%), acute fatty liver of pregnancy (AFLP) 7 (7.4%), and intrahepatic cholestasis of pregnancy 1 (1.1%). When compared to HELLP syndrome, AFLP showed significantly higher median (IQR) values (p<0.05) for total bilirubin 13.3 (7.3-16.3), direct bilirubin 9.73 (6.87-11.9) mg/dL, prothrombin time 23 (20.4-25.7) seconds, international normalization ratio 2.2 (1.9-2.4), white blood count 23.8 (17.8-26.6)∗103/μL, creatinine 3.5 (2.44-5.6) mg/dL, and lower hemoglobin level of 7.9 (6.2-10) g/dL. There were 4 (4.2%) maternal hospital deaths, with a case fatality rate of HELLP syndrome being 8.6% and 14.3% in AFLP. The overall hospital fetal mortality was 33 (34.7%). In this study, 42 patients with HELLP syndrome and AFLP had an increased risk of maternal ICU admission (OR=25.5, 95% CI: 5.48-118.6, p value = 0.001), acute kidney injury requiring dialysis (OR=12.2, 95% CI: 1.46-102.2, p value = 0.009), placental abruption (OR=14.2, 95% CI: 1.72-117.1, p value = 0.004), and stillbirth (OR=7.2, 95% CI: 2.38-21.7, p value = 0.001). Conclusion. Preeclampsia with liver dysfunction and HELLP syndrome accounted for the majority of cases. It also demonstrated key biochemical characteristics that can be used to distinguish between HELLP syndrome and AFLP. Emphasis has to be given to the risk of requiring maternal ICU admission, dialysis, abruption of the placenta, and stillbirths while managing patients diagnosed with HELLP syndrome and AFLP.